Cost of hospitalisation for non‐communicable diseases in India: are we pro‐poor?. Issue 8 (22nd June 2016) - Tripathy, J. P.; Prasad, B. M.; Shewade, H. D.; Kumar, A. M. V.; Zachariah, R.; Chadha, S.; Tonsing, J.; Harries, A. D.
Abstract: Objectives: To estimate out‐of‐pocket (OOP) expenditure due to hospitalisation from NCDs and its impact on households in India. Methods: The study analysed nationwide representative data collected by the National Sample Survey Organisation in 2014 that reported health service utilisation and healthcare‐related OOP expenditure by income quintiles and by type of health facility (public or private). The recall period for inpatient hospitalisation expenditure was 365 days. Consumption expenditure was collected for a recall period of 1 month. OOP expenditure amounting to >10% of annual consumption expenditure was termed as catastrophic. Weighted analysis was performed. Results: The median expenditure per episode of hospitalisation due to NCDs was USD 149 – this was ~3 times higher among the richest quintile compared to poorest quintile. There was a significantly higher prevalence of catastrophic expenditure among the poorest quintile, more so for cancers (85%), psychiatric and neurological disorders (63%) and injuries (63%). Mean private‐sector OOP hospitalisation expenditure was nearly five times higher than that in the public sector. Medicines accounted for 40% and 27% of public‐ and private‐sector OOP hospitalisation expenditure, respectively. Conclusion: Strengthening of public health facilities is required at community level for the prevention, control and management of NCDs. Promotion of generic medicines, better availability of essential drugs and possible subsidisation for the poorest quintile will be measures to consider to reduce OOP expenditure in public‐sector facilities.